Polyethyleneimine functionalized platinum superstructures: enhancing hydrogen evolution performance by morphological and interfacial control - Xu, Guang-Rui (2018)
The electrocatalytic hydrogen evolution reaction (HER) is a highly promising green method for sustainable and efficient hydrogen production. So far, Pt nanocrystals are still the most active electrocatalysts for the HER in acidic media, although a tremendous search for alternatives has been done in the past decade. In this work, we synthesize polyethyleneimine (PEI) functionalized Pt superstructures (Pt-SSs@PEI) with tetragonal, hierarchical, and branched morphologies with a facile wet chemical reduction method. A series of physical characterizations are conducted to investigate the morphology, electronic structure, surface composition, and formation mechanism of Pt-SSs@PEI. Impressively, the as-prepared Pt-SSs@PEI show an unprecedented onset reduction potential (+64.6 mV vs. reversible hydrogen electrode) for the HER in strong acidic media due to the protonation of –NH2 groups in the PEI adlayers on the Pt surface, and they outperform all currently reported HER electrocatalysts. The work highlights a highly effective interface-engineering strategy for improving the electrocatalytic performance of Pt nanocrystals for the HER.